Perineal myxoid liposarcoma: report of a case and literature review - Ramasamy, Prabhu; Md Nor, Azmi; Harun, Norra; Mohd Yusof, Mubarak; Mat Hassan, Mohd. Zailani (2010)
Liposarcomas are rare soft tissue tumour, with an incidence of 30 cases per million population. The myxoid liposarcoma (MLS) consists of 45 – 55% of these tumours, making it the most common subtype. MLS commonly involves the thigh and retroperitoneum but relatively rare in the perineum or pararectal spaces. MLS presents with unique radiological challenges and have the potential for overt malignant behaviour. The determination of clinical behaviour and pathological subtype is invaluable to the management of these patients, as there is no available consensus on the use of neoadjuvant and adjuvant therapies in the form of chemotherapy or radiotherapy for non-metastatic soft tissue sarcomas. Therefore, surgery remains the mainstay of treatment for MLS. We presents an unusual case of myxoid liposarcoma presenting as a large perineal swelling occupying the para-rectal and para-anal spaces. The diagnosis, management and prognosis of myxoid liposarcoma are discussed.